Factors of Resistance to Global Economic Threats - S. V. Kazantsev (Мир новой экономики)
In the process of evolution, all living beings on our planet are exposed to internal and external forces, conditions and circumstances, which are adverse, harmful and dangerous for its existence and reproduction. In the field of economy, these are periodic crises of overproduction, fair and unfair competition, various prohibitions, blockades and sanctions. The purpose of this paper is to determine the conditions, forces and circumstances (resistance factors), which ensure the resistance of the country, its economy and the state to such harmful effects, that can cause damage, disrupt and even interrupt the process of normal development. In our days, such damage to the economy of a country may be caused by various types of sanctions, imposed, as a rule, by a group of States against legal entities and persons of any country. The author of this paper discusses three areas of finding sources of resilience. They are habitat, endangered object (in our case — society), available means of protection. These areas were chosen because resistance to harmful effects and elimination of their consequences is carried out, first of all, by the object of such effects: society of people engaged in the conscious economic activity; a habitat of human society; and, finally, the resources and protection means which are available to society.